2017
DOI: 10.1353/hpu.2017.0133
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences (ACE) among American Indians in South Dakota and Associations with Mental Health Conditions, Alcohol Use, and Smoking

Abstract: American Indians in South Dakota experience more ACEs, which may contribute to poor behavioral health. Preventing and mitigating the effects of ACEs may have a significant impact on health disparities in AI populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 49 publications
1
55
0
Order By: Relevance
“…RRs, HRs, or ORs were extracted at each available ACE count level (adjusted for demographics and socioeconomic status where available; table 1). [3][4][5][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] All articles reported some sociodemographic adjustments and adjusted ORs were transformed into RRs by use of the equation: RR=OR/(1 − p 0 + [p 0 × OR]), where p o is the baseline risk in the absence of ACEs. 37 Adjusted positive and negative counts by condition and ACE category were also generated for use in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RRs, HRs, or ORs were extracted at each available ACE count level (adjusted for demographics and socioeconomic status where available; table 1). [3][4][5][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] All articles reported some sociodemographic adjustments and adjusted ORs were transformed into RRs by use of the equation: RR=OR/(1 − p 0 + [p 0 × OR]), where p o is the baseline risk in the absence of ACEs. 37 Adjusted positive and negative counts by condition and ACE category were also generated for use in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We accounted for this overlap by excluding risk factor DALYs captured in causes before calculating DALY totals. Although most studies controlled for age and socioeconomic groups, four studies 22,28,35,36 did not account for both (table 1). We did not adjust our analysis for study quality, but one study 35 consistently reported lower risk estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Given the well-documented association between ACEs and poor physical and mental health, the prevalence of child maltreatment raises great public health and economic concerns (https://www.acf. [12] The disproportionate exposure to ACEs in certain marginalized populations may exacerbate health disparities, [13] and be transmitted intergenerationally, thus compounding the effects of the initial adversities. In the United States (U.S.) alone, an estimated four million suspected cases of abuse and neglect are referred yearly to child protective services agencies (https://www.…”
mentioning
confidence: 99%
“…Established in 2011, NIEJI addresses the lack of culturally appropriate information and community education on elder abuse, neglect, and exploitation in American Indian communities. Efforts to deliver services in these communities is critical in light of fi ndings such as higher rates of adverse childhood experiences among American Indians compared to non-American Indians, which are attributable to incidences of emotional and physical abuse and neglect [75]. EJIG contributes to the improvement of the fi eld of elder maltreatment at large by developing materials, interventions, or programs that can be widely disseminated and/or replicated and by establishing and/ or contributing to the evidence base of knowledge.…”
Section: Federal Programs Initiatives and Servicesmentioning
confidence: 99%